Perancangan Rumah Hijau di Kelurahan Gongdrong Kecamatan Cipondoh Kota Tangerang - Aldo Naufaldo; Sri Kurniasih; Tri Endangsih (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2023)
Fulfillment of development needs in the context of economic growth is often carried out without regard to environmental conditions. Likewise, remnants of expositions/activities in every building that are not managed properly will pollute the surrounding environment which of course has a negative impact on life. The reduction in productive land and the narrowing of green open spaces as water catchment areas are also the driving factors for the emergence of the green structure movement. With the design of the green house area in Gondrong Village, it is hoped that it can reduce the effects of Global Warming which is currently happening, and that less land is used in accordance with local government regulations. Green Architecture is here to solve a problem that occurs in Gondrong Village.